Desain Pengembangan Buku Ajar Akidah Akhlak Berbasis QR Code Kelas XI MA Mambaul Ulum Jombang - Aisa, Aufia; Chasanah, Cholifatu Niswatin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
In order to meet the challenges of 21st century learning and develop character education in schools, innovation is needed to realize these educational goals. Therefore, researchers are trying to provide a solution by conducting development research with QR Code-based learning media. The product produced in this research is a QR Code-based Aqidah Akhlak textbook for class XI MA. The subjects in this research were class XI students at MA Mambaul Ulum Megaluh Jombang with a total of 20 students. Data collection techniques in this research are observation, interviews, distribution of questionnaires, and documentation. The types of data used by researchers are qualitative data and quantitative data. The data collection instruments used were material expert validation sheets and student questionnaires. Based on the validation of the material expert's assessment results, a score of 53 was found to be appropriate, and from the media expert's assessment, a score of 79 was found to be very appropriate, and from validation of the students' results, a score of 51 was declared to be appropriate. So it can be concluded that the PAI textbook with the QR Code-based Aqidah Morals subject is effective and suitable for use by students at MA Mambaul Ulum Megaluh Jombang.